Proteomic Characterization of the Heart and Skeletal Muscle Reveals Widespread Arginine ADP-Ribosylation by the ARTC1 Ectoenzyme - Mario Leutert; Stephan Menzel; Rickmer Braren; Björn Rissiek; Ann-Katrin Hopp; Kathrin Nowak; Lavinia Bisceglie; Peter Gehrig; Hui Li; Anna Zolkiewska; Friedrich Koch-Nolte; Michael O. Hottiger (Cell Reports, 2018)
Summary: The clostridium-like ecto-ADP-ribosyltransferase ARTC1 is expressed in a highly restricted manner in skeletal muscle and heart tissue. Although ARTC1 is well studied, the identification of ARTC1 targets in vivo and subsequent characterization of ARTC1-regulated cellular processes on the proteome level have been challenging and only a few ARTC1-ADP-ribosylated targets are known. Applying our recently developed mass spectrometry-based workflow to C2C12 myotubes and to skeletal muscle and heart tissues from wild-type mice, we identify hundreds of ARTC1-ADP-ribosylated proteins whose modifications are absent in the ADP-ribosylome of ARTC1-deficient mice. These proteins are ADP-ribosylated on arginine residues and mainly located on the cell surface or in the extracellular space. They are associated with signal transduction, transmembrane transport, and muscle function. Validation of hemopexin (HPX) as a ARTC1-target protein confirmed the functional importance of ARTC1-mediated extracellular arginine ADP-ribosylation at the systems level. : Leutert et al. identify the ADP-ribosylomes of skeletal muscle and heart tissue and show that they comprise mainly arginine modification sites that are modified by the ADP-ribosyltransferase ARTC1. The functional importance of ARTC1 is documented by impaired muscle performance in ARTC1-deficient mice and tuning of heme binding by hemopexin ADP-ribosylation in vitro. Keywords: ADP-ribosylation, proteomics, mass spectrometry, post-translational modification, ARTC1, arginine modification, muscle, heart, C2C12, hemopexin